Pelayanan Kesehatan Terhadap Lansia Dalam Meningkatkan Kualitas Hidup Di Kelurahan Meruya Selatan Jakarta - Sisca; Monica Dwi Hartanti; Orliando Roeslan; David; Yani Kurniawan; ML Edy Parwanto; Joey Joshua Vidova Tjahyadi (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Elderly people are part of the life process that cannot be avoided and will be experienced by every human being. Objective: to help the elderly community in the area of the Lukas Church of Maria Kusuma Karmel Parish, West Jakarta, Meruya Selatan Subdistrict to improve their quality of life, especially in the physical domain, through counseling activities, health services and treatment so that it is hoped that it can improve the quality of life of the elderly. Method: Health services were provided to 60-70 elderly people in South Meruya Village. The service team consists of 6 lecturers and 3 students. Blood pressure, height and weight, glucose, uric acid and cholesterol were measured. Results: High blood pressure was checked for around 37% of elderly people, 33% for cholesterol, 10% for glucose and 57% for uric acid. Conclusion: Regular health checks are an important part of comprehensive prevention and management of chronic diseases. Family and local community support can help elderly residents undergo treatment to improve their quality of life.